An Examining the Role of Clinical Supervision in Developing Rational Emotive Behavior Counseling Skills - Hidayah, Nur; Ramli, M.; Fauzan, Lutfi; Wahyuni, Fitri; Yunita, Mila; Hanafi, Husni; Kurniawan, Nanda Alfan (Bisma The Journal of Counseling, 2025)
The effectiveness of clinical supervision in enhancing counselors' competencies in practicing Rational Emotive Behav-ior Counseling (REBC) remains largely unexplored. This study aims to evaluate and optimize the impact of clinical supervision on counselors' skills in REBC, particularly in developing diagnostic abilities, accuracy in disputing, and the effectiveness of technique implementation. A pre-experimental design with a quasi-experimental approach was employed. The instruments used included an REBC counseling competence evaluation and a counseling perfor-mance observation sheet. The data were analyzed descriptively.The results indicate that clinical supervision plays a significant role in improving counselors' competencies, especially in diagnostic skills, followed by an increase in dis-puting abilities. However, improvements in the effectiveness of technique implementation remain relatively low. A limited sample size is one of the constraints of this study in terms of generalizing the findings. Nevertheless, the de-scriptive results provide a reasonable overview of the impact of the supervision program on REBC counseling skills. Future research is recommended to consider sample dynamics, a time-series design, and consistency analysis through trend and graphical approaches.